Body Beautiful : studies in masculine art. (Jersey : Body Beautiful Publications, 1955)
Fonds Suzan Daniel (FSD)
F/02/016 Archief Roger Vertongen
Periodiciteit : tweemaandelijks
Redactie : 16, Hopkins Avenue, Jersey City ; vanaf (1958) Palisade Avenu 801, Union City (California)
Engels
Periodiek